Daily stress, problematic social media use, and executive functions: A daily diary approach - NG, Wee Qin (Institutional Knowledge at Singapore Management University, 2024)
A growing body of research suggests that daily stress may be a risk factor for problematic social media use. However, findings concerning the relation between stress and social media use are mixed, suggesting the presence of moderators that may buffer the relation between stress and problematic social media use. Further, previous studies have relied on either cross-sectional designs or longitudinal designs that may not fully capture daily experiences of stressors and social media use. To overcome these limitations, the present study utilized a 7-day daily diary study to investigate the within-individual associations between daily stress and problematic social media use. Drawing on the Interaction of Person-Affect-Cognition-Execution (I-PACE) model, I examined whether executive functions (i.e., EF) – a set of cognitive processes crucial for regulated, goal-directed behaviors – would moderate the link between daily stress and problematic social media use. 253 college students completed daily measures assessing daily stressors and problematic social media use symptoms and provided daily uploads of their time spent on social media applications. In addition, participants completed nine cognitive tasks measuring the three EF constructs of inhibition, updating, and shifting. Multilevel modelling revealed that participants’ average stress levels predicted greater frequency of problematic social media use. Importantly, inhibition moderated the relation between daily stress and daily social media screentime, suggesting that individuals with better inhibition abilities may be more adept at resisting social media use in response to stressors. These findings highlight the importance of inhibition in buffering against the detrimental influences of daily stress on daily social media use.